ANALISIS IMPLEMENTASI SISTEM INFORMASI AKUNTANSI DENGAN MENGGUNAKAN SOFTWARE ACOSYS PADA PT LADFANID KONSULTINDO BATAM - Argo Putra Prima; Jefri Akbar (LPPM Universitas Putera Batam, 2020)
The purpose of this study is to examine the use of an accounting system using Microsoft Excel, the reliability of the accounting system used previously as well as the factors that influence the successful implementation of the Acosys software-based accounting information system at PT Ladfanid Konsultindo Batam. In implementation, in Microsoft Excel presenting financial statements, especially for trading and manufacturing companies in the calculation of cost of goods sold, there must be a classification beforehand because Microsoft Excel does not have a special menu in the presentation of purchases and sales so that there are several classifications in different sheets. The accounting system used today is Acosys, which is an accounting system that is more adequate and reliable than using Microsoft Excel. Acosys can be categorized as a complex system in preparing financial statements because it has features that can be used according to company needs. every transaction that has been inputted automatically all kinds of reports relating to finance can be accessed quickly as needed. What is rarely owned by other software but owned by Acosys is that Acosys software can be used forever without additional costs for updating.